Proteus mirabilis exacerbates ulcerative colitis by inhibiting mucin production - Jiang, Zhihui; Li, Pengpeng; Qiu, Kehui; Liao, Yang; Chen, Xin; Xuan, Ji; Wang, Fangyu; Ma, Hongfeng; Wang, Ye; Zhu, Minsheng (Frontiers in Microbiology, 2025)
IntroductionUlcerative colitis (UC) is characterized by chronic inflammation and ulceration in colonic mucosa, accompanied by a defective epithelial barrier. Proteus mirabilis (P. mirabilis) bacterium is a putative intestinal pathogen with invasive ability, yet its role in UC inflammation and gut barrier disruption is unclear. This study aims to investigate its epidemiological presence, pathogenic roles and preventive strategy during UC inflammation.MethodP. mirabilis culture and PCR amplification of the P. mirabilis-specific ureR gene were used to detect fecal P. mirabilis and determine its prevalence in UC and control stool specimens. P. mirabilis isolated from UC stool specimens was gavaged into dextran sulfate sodium (DSS)-treated mice. Inflammation and the mucus layer of colons were assessed through histological examination and cytokine quantification. Bacteriophages were screened and used to eliminate P. mirabilis in colitis animals.Results and discussionThe fecal P. mirabilis bacteria were detected by PCR amplification of P. mirabilis-specific ureR gene. Of 41 UC patients, 65.9% patients were P. mirabilis positive, which was significantly higher than the controls. Administration of P. mirabilis aggravated DSS-induced colitis symptom and mucosal inflammation in mice. Interestingly, the colonic mucus layer, an essential component of the epithelial barrier, of the animals was dramatically disrupted, which was consistent with the alteration of human UC colon. The disrupted mucus layer was mediated by the down-regulation of IL-18 in intestinal epithelium. Importantly, a bacteriophage cocktail targeting P. mirabilis could restore the mucus barrier and alleviate the enteric inflammation. Thus, our results suggest that P. mirabilis is a UC pathobiont bacterium, which exacerbates the severity of UC inflammation owing to down-regulation of mucin production and IL-18 expression. Bacteriophage-mediated elimination of P. mirabilis may be effective in limiting UC inflammation.